2008
DOI: 10.1073/pnas.0800979105
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression-based screening identifies microtubule inhibitors as inducers of PGC-1α and oxidative phosphorylation

Abstract: The transcriptional coactivator PGC-1␣ is a potent regulator of several metabolic pathways, including, in particular, the activation of oxidative phosphorylation and mitochondrial biogenesis. Recent evidence suggests that increasing PGC-1␣ activity may have beneficial effects in various conditions, including muscular dystrophy, diabetes, and neurodegenerative diseases. We describe here a high-throughput screen to identify small molecules that induce PGC-1␣ expression in skeletal muscle cells. A number of drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 42 publications
1
61
0
Order By: Relevance
“…From a mechanistic perspective SIRT1 has also been shown to enhance insulin sensitivity in insulin-resistant myotubes via repression of the protein-tyrosine phosphatase 1B (37). Recently, small molecule activators of PGC-1␣ itself has been described (38). These compounds need to be explored as alternative agents to modify this program in skeletal muscle and to evaluate whether they too can restore insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanistic perspective SIRT1 has also been shown to enhance insulin sensitivity in insulin-resistant myotubes via repression of the protein-tyrosine phosphatase 1B (37). Recently, small molecule activators of PGC-1␣ itself has been described (38). These compounds need to be explored as alternative agents to modify this program in skeletal muscle and to evaluate whether they too can restore insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This screening technique demonstrated that PGC-1␣ expression can be regulated by microtubule and protein synthesis inhibitors (Arany et al, 2008). Although these compounds do not harbor significant therapeutic potential, the technique demonstrates the ability to screen for inducers of PGC-1␣, and screening larger libraries may ultimately provide new useful inducers of PGC-1␣.…”
mentioning
confidence: 99%
“…Spiegelman and colleagues recently developed a quantitative PCR screen to identify inducers of PGC-1␣ expression (Arany et al, 2008). This screening technique demonstrated that PGC-1␣ expression can be regulated by microtubule and protein synthesis inhibitors (Arany et al, 2008).…”
mentioning
confidence: 99%
“…Mixed results have been obtained with the fibrate drug bezafibrate, a pan-peroxisome proliferator-activated receptor agonist (Wenz et al, 2008;Romanino et al, 2011;Yatsuga and Suomalainen, 2012). A recent high-throughput screen in murine primary skeletal muscle cells elucidated several distinct classes of drugs promoting MB; however, several of these, including glucocorticoids and inhibitors of microtubules and protein synthesis, would not be suitable for clinical administration due to toxicity and side effects (Arany et al, 2008).…”
Section: Introductionmentioning
confidence: 99%